Let's look at the steps in the problem-solving process for the equation \(3x + 2x - 6 = 24\) and identify where the mistake occurred.
-
Start with the original equation: \[ 3x + 2x - 6 = 24 \]
-
Combine like terms on the left side. The terms \(3x\) and \(2x\) can be added together: \[ 5x - 6 = 24 \]
-
The next step should involve isolating \(x\). The incorrect solution showed: \[ -2x - 2x \] This step is incorrect. Instead of subtracting \(2x\) from both sides, you should add \(6\) to both sides to isolate the term with \(x\): \[ 5x - 6 + 6 = 24 + 6 \]
This simplifies to: \[ 5x = 30 \]
-
Then, divide both sides by \(5\) to solve for \(x\): \[ x = \frac{30}{5} = 6 \]
So, the mistake in the original solution was incorrectly subtracting \(2x\) instead of correctly adding \(6\) to isolate the \(5x\) term. This led to the wrong conclusion that \(x = 30\). The correct answer is \(x = 6\).